MANAGEMENT OF THE TIBIAL SHAFT FRACTURES WITH A SUPRAPATELLAR APPROACH - AM, ILIAS BASHA; KB, VIJAYA MOHAN REDDY; KUMAR, GURRAM MADHAN; SHANMUGAVELU, SUJIN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Tibia fractures are the most common long bone fractures, among which diaphyseal fractures are more common. Tibial diaphyseal fractures have a significant risk of non-union and malunion among all long bone fractures. Among adults, IMILN is the treatment of choice for unstable and displaced fractures. The traditional surgical method is the infrapatellar approach, which has its own drawbacks. Here, we are studying the suprapatellar approach. Methods: The prospective study was conducted on 25 patients in the Department of Orthopedics, Government General Hospital, Kurnool for 1 year from November 2022 to November 2023. Patients were examined clinically and functional outcomes were noted. Results: The suprapatellar approach shows an average operative time was 40–80 min and blood loss was around 70–90 mL. The mean time of union was 15–16 weeks. Conclusion: For tibial diaphyseal fractures, the suprapatellar approach is a safe and effective alternative nail insertion.